Analisis Pengaruh Kapur Tohor (CaO) dan Tawas Terhadap Parameter TSS dan pH di Desa Huta Dame Kecamatan Penyabungan Utara Kabupaten Mandailing Natal - Tambunan, Yunita Kristina (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The people's gold mining activities in Huta Dame Village, Kotanopan Utara District, Mandailing Natal are still very simple. The purpose of this study was to analyze the TSS and pH parameters around the gold mining area so that they comply with quality standards. This research method is by interviews and direct observation to the field. The results of the analysis showed that the quality of acid mine drainage before treatment was 4.26 and after the addition of quicklime in 1 gram it was still acidic but in the addition of quicklime in the 65th minute (3 grams) a pH of 6.02 was obtained and it met the quality standard. The addition of 1 and 3 grams of alum is still acidic and this can cause the air in the mining environment to be corrosive due to the large amount of heavy metals originating from rocks which can cause environmental damage, due to excessive use of mercury resulting in the emergence of acid mine drainage. The addition of 1 and 3 grams of quicklime, TSS values 48 & 38 mg/l . The TSS values for the addition of 1 & 3 grams of alum were 20 & 28 mg/l and met the quality standards. Thus the use of quicklime in gold mining waste is more effective than the use of alum as an acid mine drainage treatment method.